Answer:
9
Step-by-step explanation:
Let's first convert this to numbers. When a number is decreased by a certain amount, that is the same as saying that something is subtracted from it. Therefore:
a-7=2
Add 7 to both sides:
a-7+7=2+7
a=9
Hope this helps!
Answer:
What did you do? What is this mess but thanks for the points
Step-by-step explanation:
It is called a ray. Which is what you described
Answer:
x = 4
y = 1
Step-by-step explanation:
Here, we want to solve the system of equation using elimination method
We have this as follows;
3x + y = 13
4x- 3y = 13
Multiply equation 1 by 3
9x + 3y = 39
4x-3y = 13
Add the two equations
13x = 52
x = 52/13
x = 4
From equation 1;
3x + y = 13
y = 13-3x
y = 13-3(4)
y = 13-12 = 1
Answer:
nth term = 1 + n(13/4)
Step-by-step explanation:
3n + n/4 + 1
n = 1, 3(1) + (1)/4 + 1 = 4 + ¼ = 17/4
n = 2, 3(2) + (2)/4 + 1 = 7 + ½ = 30/4
n = 3, 3(3) + (3)/4 + 1 = 10 + ¾ = 43/4
n = 4, 3(4) + (4)/4 + 1 = 14 = 56/4
The difference between consecutive terms is 13/4
At n = 1, 17/4 = 1 + 1(13/4)
At n = 2, 30/4 = 1 + 2(13/4)
nth term = 1 + n(13/4)